The resilience of Islamic banks and conventional banks in the global financial crisis - Seyed Hossein Mirjalili (Iranian Association of Islamic Finance, 2016)
Islamic banks had demonstrated significant resilience during the global financial crisis, because of relying on real economic activities, avoiding toxic financial derivatives, and keeping higher liquid assets. However, they were vulnerable afterward in economic crisis. Canadian banks as an example of the most successful conventional banks during both the global financial and economic crisis, also had demonstrated significant resilience, because of institutional setting, prudential regulator, high capital asset ratio, leverage cap, and conservative mortgage market. Islamic banks can learn from this experience and make a reform on liquidity management, corporate governance and consider the experience of resilience conventional banks.
Conference: First Conference of Islamic Finance, 27th of December 2015, Alzahra University
Keywords: 330; Islamic banks; Conventional banks; global financial crisis; resilience